2021
DOI: 10.1017/jns.2021.75
|View full text |Cite
|
Sign up to set email alerts
|

Camel milk consumption is associated with less childhood stunting and underweight than bovine milk in rural pastoral districts of Somali, Ethiopia: a cross-sectional study

Abstract: Undernutrition is a major global health problem. Various types of animal milk are used for feeding children at early ages; however, associations of camel milk (CaM) and bovine milk (BM) with the nutritional status of children have not been explored. A comparative community-based cross-sectional study was conducted among pre-schoolers in rural pastoral districts of Somali, Ethiopia. Children were selected from households with lactating camels or cows. Anthropometric measurements followed standard procedures for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Some studies had multiple outcomes. For the nutritional outcomes measured, dietary diversity was reported by 9% ( n = 5) of the studies ( 46 50 ), consumption of ASFs by 18% ( n = 10) of the studies ( 27 , 46 , 50 57 ), hemoglobin concentration and prevalence of anemia by 7% ( n = 4) of the studies ( 51 , 58 60 ), stunting or HAZ z-scores by 33% ( n = 18) of the studies ( 27 , 46 48 , 51 53 , 55 57 , 61 68 ), wasting or WHZ z-scores by 15% ( n = 8) of the studies ( 27 , 46 , 47 , 51 , 55 57 , 61 ), and 18% ( n = 10) reported on underweight or WAZ z-scores ( 27 , 46 48 , 53 , 60 , 61 , 68 70 ) Based on study design, of the 29 studies reviewed, 14% ( n = 4) were livestock oriented impact evaluations, 4% ( n = 1) evaluated dairy sensitive value chains, 41% ( n = 12) were observational studies, and 41% ( n = 12) were experimental studies ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies had multiple outcomes. For the nutritional outcomes measured, dietary diversity was reported by 9% ( n = 5) of the studies ( 46 50 ), consumption of ASFs by 18% ( n = 10) of the studies ( 27 , 46 , 50 57 ), hemoglobin concentration and prevalence of anemia by 7% ( n = 4) of the studies ( 51 , 58 60 ), stunting or HAZ z-scores by 33% ( n = 18) of the studies ( 27 , 46 48 , 51 53 , 55 57 , 61 68 ), wasting or WHZ z-scores by 15% ( n = 8) of the studies ( 27 , 46 , 47 , 51 , 55 57 , 61 ), and 18% ( n = 10) reported on underweight or WAZ z-scores ( 27 , 46 48 , 53 , 60 , 61 , 68 70 ) Based on study design, of the 29 studies reviewed, 14% ( n = 4) were livestock oriented impact evaluations, 4% ( n = 1) evaluated dairy sensitive value chains, 41% ( n = 12) were observational studies, and 41% ( n = 12) were experimental studies ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our evidence synthesis, a sizeable percentage of articles showed that livestock interventions improved access to and consumption of nutrient-dense animal-source foods ( 27 , 46 , 50 57 ), attaining minimum dietary diversity ( 46 50 ), hemoglobin concentration, and prevalence of anemia ( 51 , 58 60 ). Additionally, some livestock interventions improved children’s stunting or height-for-age (HAZ) z-scores ( 27 , 46 48 , 51 53 , 55 57 , 61 68 ), wasting or weight-for-height (WHZ) z-scores ( 27 , 46 , 47 , 51 , 55 57 , 61 ), and underweight or weight-for-age (WAZ) z-scores ( 48 , 61 , 68 , 69 ), which are indicators of chronic and acute nutritional status in children.…”
Section: Discussionmentioning
confidence: 99%
“…Stunting will reduce productivity as adults and cause a decrease in human resources always in the future (Sjarif et al 2019). Childhood stunting has significant and long-term consequences for individuals, families, and countries (Muleta et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Stunting in children is mostly caused by poor nutrition, a high disease burden, inadequate child feeding, poor sanitation, and a lack of access to high-quality health and nutrition services (Muleta et al 2021). For children's growth and development, an adequate intake of macro-and micronutrients (such as energy, protein, and vitamins A, C, and calcium) is important.…”
Section: Introductionmentioning
confidence: 99%